Kejadian Gingivitis pada Siswa Tunagrahita di SLB Wilayah Pesisir Kota Manado - Pardanus, Darlene G.; Tendean, Lydia E. N.; Mintjelungan, Christy N. (Universitas Sam Ratulangi, 2026)
Abstract: Gingivitis is one of the periodontal disease characterized by redness, swelling of the gingival tissue, and bleeding due to the accumulation of dental plaque and calculus in the supragingival and subgingival areas. This disease is common among children, including those with special needs such as individuals with intellectual disabilities. Children with intellectual disabilities face challenges in maintaining oral hygiene due to intellectual and behavior limitations, which increase the risk of periodontal diseases like gingivitis. Moreover, socioeconomic challenges and limited access to dental health services in coastal areas further exacerbate this condition. This study aimed to determine the incidence of gingivitis in students with intellectual disabilities in special schools at the coastal area of Manado City. This was an observational study with a cross-sectional design conducted on students with intellectual disabilities at GMIM Nazareth Tuminting Special School and YPAC Special School in Manado using the total sampling method. The results obtained 46 students as respondents; females (58.7%) were more frequent than males (41.3%). The highest percentages were students from SMPLB and SMALB (each of 34.8%). The majority of respondents suffered from gingivitis (89.1%), especially on both upper and lower jaws (41.3%). In conclusion, the prevalence of gingivitis among intellectually disabled students in Special Schools in the coastal area of Manado City is categorized as high (89.1%). Keywords: gingivitis; students with intellectual disabilities Abstrak: Gingivitis merupakan salah satu penyakit periodontal yang ditandai dengan kemerahan, pembengkakan jaringan gingiva, dan pendarahan akibat penumpukan plak gigi dan kalkulus di supragingiva dan subgingiva. Gingivitis menjadi salah satu penyakit periodontal yang umum terjadi pada anak, termasuk mereka yang memiliki kebutuhan khusus seperti tunagrahita. Anak-anak tunagrahita menghadapi tantangan dalam menjaga kebersihan gigi dan mulut akibat keterbatasan intelektual dan perilaku adaptif, yang meningkatkan risiko terhadap penyakit periodontal seperti gingivitis. Tantangan sosial ekonomi dan keterbatasan akses terhadap layanan kesehatan gigi di wilayah pesisir memperburuk kondisi ini. Penelitian ini bertujuan untuk mengetahui kejadian gingivitis pada siswa tunagrahita di Sekolah Luar Biasa wilayah pesisir Kota Manado. Jenis penelitian ialah observasional dengan desain potong lintang yang dilakukan pada siswa tunagrahita di SLB GMIM Nazareth Tuminting dan SLB YPAC Kota Manado dengan metode total sampling. Hasil penelitian mendapatkan 46 siswa sebagai responden penelitian. Responden perempuan (58,7%) lebih banyak daripada laki-laki (41,3%), terbanyak berada di tingkat SMPLB dan SMALB (masing-masing 34,8%). Mayoritas responden mengalami gingivitis (89,1%), terutama pada rahang atas dan bawah (41,3%). Simpulan penelitian ini ialah angka kejadian gingivitis pada siswa tunagrahita di sekolah luar biasa wilayah pesisir Kota Manado tergolong tinggi (sebesar 89,1%). Kata kunci: gingivitis; siswa tunagrahita